2020
DOI: 10.1002/cncy.22345
|View full text |Cite
|
Sign up to set email alerts
|

The value of a tiered cytology diagnostic reporting system in assessing the risk of malignancy in indeterminate serous effusions

Abstract: Background The International System for Reporting Serous Fluid Cytopathology was recently proposed as a tiered structure to provide consistent reporting terminology for serous effusions. Because of the variation in reporting practices for indeterminate serous effusions, namely, the atypia of undetermined significance (AUS) and suspicious for malignancy (SFM) groups, the authors retrospectively reviewed cases in these 2 categories at their institution and determined the associated risk of malignancy (ROM). Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 21 publications
11
55
4
Order By: Relevance
“…In the present study on pleural fluid samples, the calculated ROM for the categories AUS and SFM were 88.23% and 87.5%, respectively, similar to the high ROMs (AUS 71.8% and SFM 75.9%) calculated in the meta-analysis conducted by Farhani et al 8 (Table 4) In our study, The difference between the ROMs for the two categories was insignificant with the p-value of 0.78, which raises the dilemma regarding the exclusivity of these groups, is contrary to the findings by Hou et al 9 where they established that the two diagnostic categories are mutually independent groups. Moreover, the calculated ROM for the categories ND, AUS, and SFM are not significantly different from each other (Table 2), indicating that the criteria laid down for these groups must be reviewed, and more elaborative and strict criteria are laid down.…”
Section: Genitourinary Carcinomasupporting
confidence: 53%
See 1 more Smart Citation
“…In the present study on pleural fluid samples, the calculated ROM for the categories AUS and SFM were 88.23% and 87.5%, respectively, similar to the high ROMs (AUS 71.8% and SFM 75.9%) calculated in the meta-analysis conducted by Farhani et al 8 (Table 4) In our study, The difference between the ROMs for the two categories was insignificant with the p-value of 0.78, which raises the dilemma regarding the exclusivity of these groups, is contrary to the findings by Hou et al 9 where they established that the two diagnostic categories are mutually independent groups. Moreover, the calculated ROM for the categories ND, AUS, and SFM are not significantly different from each other (Table 2), indicating that the criteria laid down for these groups must be reviewed, and more elaborative and strict criteria are laid down.…”
Section: Genitourinary Carcinomasupporting
confidence: 53%
“…[1][2][3] The rationale behind this new system was derived from the already established reporting systems in cytology such as the Bethesda System (TBS) for Reporting Cervical Cytology, the Bethesda System for Reporting Thyroid Cytopathology (Bethesda Thyroid), the Paris System (TPS) for Reporting Urinary Cytology, and the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC). [4][5][6][7] This evidence-based and five-tiered system 8,9 targets the improvement of the communication between the clinicians and cytopathologists, consequently directing them to better patient management and therapeutic strategies. We present our experience with the recategorization of pleural fluid samples into the categories recommended by this classification system, highlighting the various challenges we encountered during the process.…”
mentioning
confidence: 99%
“…No other diagnostic categories were evaluated in this publication. Sensitivity and specificity values were not calculated [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent publications have looked at the risk of malignancy (ROM) for each of these categories. They have shown that values vary between affected cavities [ 5 , 6 , 17 , 18 , 19 , 20 , 21 , 22 ]. Most studies, however, were published before the development and implementation of TIS, with few exceptions [ 5 , 6 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…ROM was estimated according to the previously described methods 8,9,12 . Performance evaluation was conducted by measuring diagnostic accuracy, sensitivity, specificity, positive and negative predictive values for each pleural effusion sample 7,13 .…”
Section: Methodsmentioning
confidence: 99%